PREDICTION OF DEVELOPMENT OF CHRONIC RHINOSINUSITIS WITH NASAL POLYPS IN CHILDREN TAKING INTO ACCOUNT THE GEOMETRIC CHARACTERISTICS OF THE ETHMOID LABYRINTH - Durdona D. Alimova; Aminjon Sh. Amonov (Central Asian Journal of Medicine, 2023)
This article presents the results of forecasting and early diagnosis of CRSwNP based on studying the features of the structure of the ethmoidal cells in children using CT imaging. Area indicators of the ethmoidal cells below 41.32 sm2 are diagnostic criteria for assigning a child to the at-risk group for developing nasal polyps, while values below 28.5 sm2 allow for diagnosing CRSwNP in children.